The Telocytes in the Subepicardial Niche - Cristian Bogdan Iancu; Mugurel Constantin Rusu; Laurenţiu Mogoantă; Sorin Hostiuc; Oana Daniela Toader (Applied Sciences, 2019)
A great interest has developed over the last several years in research on interstitial Cajal-like cells (ICLCs), later renamed to telocytes (TCs). Such studies are restricted by diverse limitations. We aimed to critically review (sub)epicardial ICLCs/TCs and to bring forward supplemental immunohistochemical evidence on (sub)epicardial stromal niche inhabitants. We tested the epicardial expressions of CD117/c-kit, CD34, Cytokeratin 7 (CK7), Ki67, Platelet-Derived Growth Factor Receptor (PDGFR)-α and D2-40 in adult human cardiac samples. The mesothelial epicardial cells expressed D2-40, CK7, CD117/c-kit and PDGFR-α. Subepicardial D2-40-positive lymphatic vessels and isolated D2-40-positive and CK7-positive subepicardial cells were also found. Immediate submesothelial spindle-shaped cells expressed Ki-67. Submesothelial stromal cells and endothelial tubes were PDGFR-α-positive and CD34-positive. The expression of CD34 was pan-stromal, so a particular stromal cell type could not be distinguished. The stromal expression of CD117/c-kit was also noted. It seems that epicardial TCs could not be regarded as belonging to a unique cell type until (pre)lymphatic endothelial cells are inadequately excluded. Markers such as CD117/c-kit or CD34 seem to be improper for identifying TCs as a distinctive cell type. Care should be taken when using the immunohistochemical method and histological interpretations, as they may not produce accurate results.